Numerical Solution of the Variational PDEs Arising in Optimal Control Theory - Costanza, Vicente (2012)
An iterative method based on Picard’s approach to ODEs’ initial-value problems is proposed to solve first-order quasilinear PDEs with matrix-valued unknowns, in particular, the recently discovered variational PDEs for the missing boundary values in Hamilton equations of optimal control. As illustrations the iterative numerical solutions are checked against the analytical solutions to some examples arising from optimal control problems for nonlinear systems and regular Lagrangians in nite dimension, and against the numerical solution obtained through standard mathematical software. An application tothe (n+1)-dimensional variational PDEs associated with the n-dimensional finite-horizon time-variant linear-quadratic problem is discussed, due to the key role the LQR plays in two-degrees-of freedom control strategies for nonlinear systems with generalized costs.